Budaya Penyambutan di Sekolah Indonesia Kuala Lumpur: Upaya Membangun Lingkungan Sekolah yang Ramah dan Inklusif : Peran Guru dan Siswa dalam Membangun Budaya Ramah - Manyingarri Alfianoor Ibrahim; Devi Pramitha (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study examines the welcoming culture implemented at Sekolah Indonesia Kuala Lumpur (SIKL) as an effort to build a friendly and inclusive school environment. The welcoming culture carried out by teachers every morning aims to create a closer and more caring atmosphere, while increasing emotional conversations between teachers and students. This study uses a qualitative method with a case study approach, and was conducted through interviews with the vice principal for student affairs, students, and parents of students. The results of the study indicate that the welcoming culture has a significant impact on building students' sense of ownership of the school and strengthening communication between students and teachers. In addition, this welcoming culture also received positive appreciation from parents who saw a positive impact on changes in their children's behavior. This study suggests that a welcoming culture can be an effective strategy to create an inclusive learning environment, support students' psychosocial development, and increase their involvement in the learning process. These findings can be a reference for other schools, both in Indonesia and abroad, to adapt similar practices in an effort to create a warmer and more inclusive educational atmosphere.